Do the everyday experiences of people with severe mental illness who are “hard to engage” reflect a journey of personal recovery? - Milbourn, Ben; McNamara, Beverley; Buchanan, Angus (Informa Healthcare, 2014)
Background: Recovery experiences should bring hope, identity, meaning and personal responsibility to the lives of people experiencing severe mental illness (SMI). Aims: To describe the recovery experiences of individuals experiencing SMI who are labelled “hard to engage” and who receive mental health assertive community treatment (ACT).Methods: A qualitative approach was used to gather descriptive data from 11 adults diagnosed with SMI who live in the community. Data were gathered over 12 months through one-to-one meetings using field notes and audio recordings. Results: Longitudinal findings provided insight into the everyday experiences and include the themes of: personal understandings of recovery, potential for agency and everyday routine. Conclusions: Opportunities for recovery experiences that hold purpose and meaning are limited for individuals receiving ACT and do not reflect definitions of personal recovery within contemporary literature. Further debate is required to address the gap between theory and the reality of recovery experiences.